Microstructuring YbRh2Si2 for resistance and noise measurements down to ultra-low temperatures. (1st December 2022) - Steppke, Alexander; Hamann, Sandra; König, Markus; Mackenzie, Andrew P; Kliemt, Kristin; Krellner, Cornelius; Kopp, Marvin; Lonsky, Martin; Müller, Jens; Levitin, Lev V; Saunders, John; Brando, Manuel
Abstract: The discovery of superconductivity in the quantum critical Kondo-lattice system YbRh2 Si2 at an extremely low temperature of 2 mK has inspired efforts to perform high-resolution electrical resistivity measurements down to this temperature range in highly conductive materials. Here we show that control over the sample geometry by microstructuring using focused-ion-beam techniques allows to reach ultra-low temperatures and increase signal-to-noise ratios (SNRs) tenfold, without adverse effects to sample quality. In five experiments we show four-terminal sensing resistance and magnetoresistance measurements which exhibit sharp phase transitions at the Néel temperature, and Shubnikov–de-Haas (SdH) oscillations between 13 T and 18 T where we identified a new SdH frequency of 0.39 kT. The increased SNR allowed resistance fluctuation (noise) spectroscopy that would not be possible for bulk crystals, and confirmed intrinsic 1 / f -type fluctuations. Under controlled strain, two thin microstructured samples exhibited a large increase of T N from 67 mK up to 188 mK while still showing clear signatures of the phase transition and SdH oscillations. Superconducting quantum interference device-based thermal noise spectroscopy measurements in a nuclear demagnetization refrigerator down to 0.95 mK, show a sharp superconducting transition at T c = 1.2  mK. These experiments demonstrate microstructuring as a powerful tool to investigate the resistance and the noise spectrum of highly conductive correlated metals over wide temperature ranges.